ANALISIS PELATIHAN DAN PENGEMBANGAN PEGAWAI BERBASIS TEKNOLOGI DI DINAS PENDIDIKAN KABUPATEN SUMEDANG - Zaenuddin; Dhesti Widya Nurhasanah Ningrum (LPPM UNSAP, 2026)
This research aims to analyze the Technology-Based Training and Development of Employees at the Education Office of Sumedang Regency. The research method used in this study is qualitative. The technique employed to determine the research subjects is purposive sampling. The research informants consist of 5 individuals, including the Head of the Office, the Secretary of the Office, the General Subsection Head, Personnel Staff, and Office Operators. The data collection techniques used include literature review and field study, which consist of observation, interviews, documentation, and triangulation. The data validity techniques employed are credibility, transferability, dependability, and confirmability. The data processing procedures in this research are data reduction, data display, and conclusion drawing/verification. Based on the research findings, it was concluded that the Analysis of Training and Development of Technology-Based Employees at the Sumedang District Education Office has been implemented quite well overall. There are obstacles in the implementation, resulting in the outcomes of technology-based employee training and development still not being optimal, which impacts the employees' skills that have not significantly improved. The obstacles faced in the implementation of training and development of employees are due to budget limitations that affect the limited training schedule and the inadequate facilities for implementing technology-based employee training and development. Efforts have been made by creating Standard Operating Procedures (SOP) for a more structured schedule and utilizing webinar platforms so that training can continue despite budget constraints